Pengembangan Aplikasi Berbasis Web untuk Monitoring dan pengelolaan Stok ATK dengan Notifikasi Otomatis dan Sistem Barcode di Bank Mandiri, Commercial Banking 5&6 - Dwi Susanto; Reza Adam Chandra Wardana; Dafa Angga Aditia; Wasis Haryono (Journal Of Informatics And Busisnes, 2024)
A web-based application for managing office supplies (ATK) inventory at Bank Mandiri, Commercial Banking 5 & 6, is designed to improve efficiency in real-time recording of incoming and outgoing items. Barcode technology is applied to minimize manual input errors, and automatic notifications are integrated to provide alerts when stock levels are low. The development method uses Rapid Application Development (RAD) due to its flexibility and fast iterations. This system supports decision-making based on more accurate data. Previous research has shown that the RAD method and similar technologies are effective in enhancing operational efficiency.